Effect of High-Flow Nasal Cannula Oxygen vs Standard Oxygen Therapy on Mortality in Patients With Respiratory Failure Due to COVID-19: The SOHO-COVID Randomized Clinical Trial - Frat, Jean-Pierre; Quenot, Jean-Pierre; Badie, Julio; Coudroy, Rémi; Guitton, Christophe; Ehrmann, Stephan; Gacouin, Arnaud; Merdji, Hamid; Auchabie, Johann; Daubin, Cédric; Dureau, Anne-Florence; Thibault, Laure; et al. (JAMA : the journal of the American Medical Association, 2022)
The benefit of high-flow nasal cannula oxygen (high-flow oxygen) in terms of intubation and mortality in patients with respiratory failure due to COVID-19 is controversial. To determine whether the use of high-flow oxygen, compared with standard oxygen, could reduce the rate of mortality at day 28 in patients with respiratory failure due to COVID-19 admitted in intensive care units (ICUs). The SOHO-COVID randomized clinical trial was conducted in 34 ICUs in France and included 711 patients with respiratory failure due to COVID-19 and a ratio of partial pressure of arterial oxygen to fraction of inspired oxygen equal to or below 200 mm Hg. It was an ancillary trial of the ongoing original SOHO randomized clinical trial, which was designed to include patients with acute hypoxemic respiratory failure from all causes. Patients were enrolled from January to December 2021; final follow-up occurred on March 5, 2022. Patients were randomly assigned to receive high-flow oxygen (n = 357) or standard oxygen delivered through a nonrebreathing mask initially set at a 10-L/min minimum (n = 354). The primary outcome was mortality at day 28. There were 13 secondary outcomes, including the proportion of patients requiring intubation, number of ventilator-free days at day 28, mortality at day 90, mortality and length of stay in the ICU, and adverse events. Among the 782 randomized patients, 711 patients with respiratory failure due to COVID-19 were included in the analysis (mean [SD] age, 61 [12] years; 214 women [30%]). The mortality rate at day 28 was 10% (36/357) with high-flow oxygen and 11% (40/354) with standard oxygen (absolute difference, -1.2% [95% CI, -5.8% to 3.4%]; P = .60). Of 13 prespecified secondary outcomes, 12 showed no significant difference including in length of stay and mortality in the ICU and in mortality up until day 90. The intubation rate was significantly lower with high-flow oxygen than with standard oxygen (45% [160/357] vs 53% [186/354]; absolute difference, -7.7% [95% CI, -14.9% to -0.4%]; P = .04). The number of ventilator-free days at day 28 was not significantly different between groups (median, 28 [IQR, 11-28] vs 23 [IQR, 10-28] days; absolute difference, 0.5 days [95% CI, -7.7 to 9.1]; P = .07). The most common adverse events were ventilator-associated pneumonia, occurring in 58% (93/160) in the high-flow oxygen group and 53% (99/186) in the standard oxygen group. Among patients with respiratory failure due to COVID-19, high-flow nasal cannula oxygen, compared with standard oxygen therapy, did not significantly reduce 28-day mortality. ClinicalTrials.gov Identifier: NCT04468126.